Makna Keterlibatan Mahasiswa dalam Organisasi di Tengah Kesibukan Akademik - Nuranggraeni, Aqilah Nisrina; Clearesta, Dania Vanda; Shiddiq, Muchammad Fahmi (Jurnal Psikologi Terapan, 2024)
This study aims to understand the meaning of student involvement in organizations amidst academic busyness. Involvement in student organizations is expected to significantly contribute to the development of academic skills and soft skills necessary for the workforce. Using a qualitative approach and phenomenological design, this research explores students' subjective experiences related to their participation in organizations. Data were collected through semi-structured interviews, allowing for an in-depth exploration of the benefits, challenges, and impacts of organizational involvement on students' academic and personal lives. Data analysis was conducted using thematic analysis techniques, resulting in patterns that describe students' experiences, including how they manage time and balance academic commitments with organizational activities. The findings indicate that involvement in organizations not only helps students develop leadership skills but also contributes to psychological well-being and the development of professional identity. This study provides recommendations for educational institutions to encourage active student participation in organizations to maximize their potential in facing challenges in higher education.